PENGARUH LAYANAN TERHADAP LAJU PERTUMBUHAN PROFIT DAN DAMPAKNYA KEPADA LOYALITAS NASABAH - Mariah, Mariah (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The purpose of this study was to determine the effect of service on the rate of profit growth and the impact on customer loyalty at PT. BWK International Tbk, Sub Branch Pesanggrahan, Jakarta. A survey quantitative method was applied in this research. Findings showed that there is no significant effect of service on rate of profit growth and customer loyalty, and there is no significant effect of profit growth rate on loyalty Keywords: service quality, profit growth, customer loyalty